2020
DOI: 10.1073/pnas.2000926117
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the OsNPF4.5 nitrate transporter reveals a conserved mycorrhizal pathway of nitrogen acquisition in plants

Abstract: Low availability of nitrogen (N) is often a major limiting factor to crop yield in most nutrient-poor soils. Arbuscular mycorrhizal (AM) fungi are beneficial symbionts of most land plants that enhance plant nutrient uptake, particularly of phosphate. A growing number of reports point to the substantially increased N accumulation in many mycorrhizal plants; however, the contribution of AM symbiosis to plant N nutrition and the mechanisms underlying the AM-mediated N acquisition are still in the early stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 64 publications
5
90
0
Order By: Relevance
“…Nitrate uptake is carried out by plasma membrane-located nitrate transporters, such as OsNPF4;5 [ 28 ]. In B. napus , we performed the subcellular localization analyses of BnaNPF proteins using the WoLF PSORT program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrate uptake is carried out by plasma membrane-located nitrate transporters, such as OsNPF4;5 [ 28 ]. In B. napus , we performed the subcellular localization analyses of BnaNPF proteins using the WoLF PSORT program.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, OsNRT1.1B , the functional homologue of AtNRT1.1 in rice, can function not only in mediating nitrate signal transduction from the plasma membrane to the nucleus, but also in integrating the nitrate and phosphate signaling networks, as well as in regulating the root microbiota to facilitate organic N mineralization in soil [ 26 , 27 ]. Very recently, Wang et al (2020) found that OsNPF4.5 plays a key role in mycorrhizal NO 3 − acquisition [ 28 ]. These studies suggest that NPFs play important roles in plant developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…through exudation that mobilises Zn in soil) that led to increased plant uptake of Zn via the direct pathway. (21). This suggests that the plant-fungal symbiosis is somewhat disrupted by the loss of MtZIP14 expression, and that the active sites of nutrient transport (arbuscules), as well as fungal resource storage units (vesicles), were not able to be produced by the fungus to the same extent due to this disruption.…”
Section: A Role For Mtzip14 In Arbuscular Mycorrhizal Zn Uptakementioning
confidence: 99%
“…Considerable progress has been made toward identifying the components involved in P and N AM associations (19)(20)(21), and a AM-specific plant Cu transporter has been recently identified (22). In order to fully exploit the AM symbiosis for improved agricultural outcomes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in P and N trigger secretion of the plant hormone strigolactones into the rhizosphere (22), which facilitates contact of fungal hyphae with the roots via stimulating hyphal branching (23). After the physical contact, the fungal hyphae grow into the cortex and form the highly-branched hyphal termini "arbuscules" where nutrient exchange between the symbionts occurs; briefly, Pi, nitrate, and ammonium are taken up from the soil by extraradical hyphae, delivered to the arbuscules, and released into the arbuscular interface (reviewed in 24) from which the plant cell takes up the nutrients via the mycorrhiza-specific transporters for Pi (25,26), nitrate (27), and ammonium (28). In return, the host supplies lipid (29)(30)(31)(32) and sugar (33) as carbon source for the fungi via the complex of half-size ABC transporters STR/STR2, a putative lipid exporter (34), and the sugar transporter SWEET (35), respectively.…”
Section: Introductionmentioning
confidence: 99%